Organic dairy farming in Bangladesh: current status, challenges and prospects - Harun, Anas Bin; Bayazid, Abdullah Al; Hoque, M Nazmul; Das, Ziban Chandra (Asian-Australasian Journal of Food Safety and Security, 2024)
Organic dairy farming (ODF) is a method of dairy production that emphasizes the use of natural and sustainable practices, aiming to minimize synthetic inputs, promote animal welfare, and protect the environment. The aim of this review is to elucidate the current status, challenges and prospects of the ODF in Bangladesh. Starting from the current situation, the challenges and future potential of the ODF are presented, as well as strategies to overcome the difficulties are also highlighted. The ODF has the great potential, challenges and opportunities in Bangladesh. This involves the production of milk, meat and dairy products using sustainable and organic practices. Farmers need certification, and challenges include limited awareness, access to organic inputs, and market demand. Government initiatives, training programs, and cooperative models can support the growth of the ODF. Market opportunities and ongoing research are essential considerations. Animals raised in the ODF systems are provided access to pasture or outdoor areas and are fed organic feed, which is free from synthetic additives, antibiotics and hormones. The transition to the ODF is driven by a combination of economic, environmental, and health-related motivations, aiming to produce dairy products in a more sustainable, economically viable and environmentally friendly manner. Organic dairy farmers prioritize the well-being of their animals and advocate for a natural environment, which is integral to animal welfare. The popularity of organic products, including meat, dairy, and value-added items, from these producers continues to rise, driven by the expanding organic market, higher prices for organic milk, and consumer preferences for products from more sustainable production systems. Despite a mammoth of challenges exist in the ODF, farmers need to implement and adhere to strict standards for organic products, animal welfare and the use of organic inputs to gain the full benefits of this sustainable farming system. This review article examines the present status of the ODF industry, emphasizing key considerations, management practices, challenges, and future prospects. It also provides insights into the relevant regulatory authorities, aiming to inform farmers and stakeholders in Bangladesh and beyond about ODF. However, there is a need for future research to concentrate on improving sustainability and efficiency within the ODF sector. Asian Australas. J. Food Saf. Secur. 2024, 8(1), 13-26